Coronary artery disease in twins. Issue 2 (February 1981) - Holmes, D R; Kennel, A J; Smith, H C; Gordon, H; Moore, S B
Abstract : In two pairs of monozygotic twins with coronary artery disease who were studied by coronary angiography, there were striking similarities in the clinical course, response to exercise, and distribution of coronary artery disease. Though it is difficult to distinguish between heredity as an independent risk factor and the other major risk factors, the similarities in each twin pair may be best explained by identical heredity.